The multiuser communication system with use of chaotic frequency modulation - Політанський, Леонід Францевич; Кушнір, Микола Ярославович; Політанський, Руслан Леонідович; Еліяшів, Олег Миронович; Невельський, Олег Олегович; Величко, Сергій Веніамінович (Eastern-European Journal of Enterprise Technologies, 2012)
The use of chaotic frequency modulation (chaotic frequency modulation – CFM) in multiuser communication is studied in the article. In the given scheme the base station gives a signal with chaotic frequency variable quantity. Users use this signal to generate their own CFM signal.